Heinrich Hermelink als Reformationshistoriker: Professor Dr. Bernd Moeller zugeeignet - Hammann, Konrad (Zeitschrift für Theologie und Kirche, 1999)
In this article, the author examines H. Hermelink's understanding of the Reformation. He shows that Hermelink developed his interpretation of the era of the Reformation in the dispute with E. Troeltsch. In conclusion, he discusses the significance of Hermelink's research for the present debate on questions of the history of the Reformation.